2013
DOI: 10.1029/2012je004283
|View full text |Cite
|
Sign up to set email alerts
|

Water interactions with micronized lunar surrogates JSC‐1A and albite under ultra‐high vacuum with application to lunar observations

Abstract: [1] Interactions of molecular water with two lunar regolith surrogates (micronized JSC-1A and albite) were examined using temperature program desorption (TPD) and diffuse reflectance infrared Fourier transform spectroscopy. TPD revealed water desorption during initial heating to 750 K under ultrahigh vacuum and diffuse reflectance infrared Fourier transform spectroscopy indicated possible water formation via recombinative desorption of native hydroxyls above 425 AE 25 K. Dissociative chemisorption of water (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 38 publications
3
43
0
Order By: Relevance
“…Other complementary works Poston et al (2012) have also presented a complementary model of solar wind implantation and OH formation. They assume that the incoming protons are captured by the regolith oxides to chemically form OH and they then follow the OH migration, diffusion, and retention path, including the creation and release of water at the surface via OH + OH recombinative desorption (Poston et al, 2013). A key difference in the two models: We herein consider only the H diffusion and retention (expanding upon Starukhina (2001Starukhina ( , 2006) that might lead to a population of loitering H while they track the sources and losses of the OH molecules.…”
Section: Polar Regionsmentioning
confidence: 99%
“…Other complementary works Poston et al (2012) have also presented a complementary model of solar wind implantation and OH formation. They assume that the incoming protons are captured by the regolith oxides to chemically form OH and they then follow the OH migration, diffusion, and retention path, including the creation and release of water at the surface via OH + OH recombinative desorption (Poston et al, 2013). A key difference in the two models: We herein consider only the H diffusion and retention (expanding upon Starukhina (2001Starukhina ( , 2006) that might lead to a population of loitering H while they track the sources and losses of the OH molecules.…”
Section: Polar Regionsmentioning
confidence: 99%
“…The chemical mechanisms that may lead to the formation of H 2 O from the interaction of solar wind protons with the surface are not fully understood and may even involve a temperature threshold that Ceres does not exceed [Poston et al, 2013]. Solar wind-generated H 2 O, on the other hand, would rapidly decrease with distance from the Sun.…”
Section: Discussionmentioning
confidence: 99%
“…Because hydroxyl is not directly released from the lunar surface, this process implies that surface OH -molecules have either recombined with one another or excess protons to form H 2 O or H 2 , or that H has been broken off of the OH -through photon stimulated desorption. In the laboratory, recombinative desorption of hydroxyl is observed at temperatures above 425 ± 25 K (Poston et al 2013b), which is hotter than the maximum observed temperature on the lunar surface (Vasavada et al 2012).…”
Section: Volatiles In the Lunar Megaregolithmentioning
confidence: 96%